Reading Struggle Stories of Role Models Can Improve Students' Growth Mindsets - Du, Xu; Yuan, Sheng; Liu, Ying; Bai, Xuejun (Frontiers in Psychology, 2021)
Previous studies have suggested that reading stories of role models can improve students’ growth mindsets. The current study aimed to investigate what types of stories can increase growth mindsets of high school students, undergraduates and graduates, and how many specific stories undergraduates with low and high perseverance need to read to improve their growth mindsets. In study 1, high school students, undergraduates, and graduates were assigned to read 5 struggle stories or 5 achievement stories of role models. Their mindsets were measured before and after reading stories. The results showed that reading struggle stories rather than achievement stories of role models increased the growth mindsets of undergraduates and graduates. In study 2, undergraduates with high and low perseverance were assigned to read 5 struggle stories or 5 achievement stories of role models. Their mindsets were measured before reading stories and after reading each story. The results showed that the growth mindsets of undergraduates with low perseverance increased after reading 2 struggle stories of role models, and increased further after reading 5 struggle stories of role models. More important, the level of growth mindsets of undergraduates with low perseverance was equal to that of undergraduates with high perseverance after reading 5 struggle stories of role models. These findings reveal that reading struggle stories of role models can improve the growth mindsets of undergraduates and graduates. Students’ personality affect the effectiveness of story-based mindset intervention.